Synesthesia and learning: a critical review and novel theory - Watson, Marcus R.; Akins, Kathleen; Spiker, Chris; Crawford, Lyle; Enns, James T. (Frontiers in Human Neuroscience, 2014)
Learning and synaesthesia are profoundly interconnected. On the one hand, the development of synaesthesia is clearly influenced by learning. Synaesthetic inducers—the stimuli that evoke these unusual experiences—often involve the perception of complex properties learned in early childhood, e.g. letters, musical notes, numbers, months of the year and even swimming strokes. Further, recent research has shown that the associations individual synaesthetes make with these learned inducers are not arbitrary, but are strongly influenced by the structure of the learnt do- main. For instance, the synaesthetic colours of letters are partially determined by letter frequency and the relative positions of letters in the alphabet. On the other hand, there is also a small, but growing, body of literature which shows that synaesthesia can influence or be helpful in learning. For instance, synaesthetes appear to be able to use their unusual experiences as mnemonic de- vices and can even exploit them while learning novel abstract categories. Here we review these two directions of influence and argue that they are interconnected. We propose that synaesthesia arises, at least in part, because of the cognitive demands of learning in childhood, and that it is used to aid perception and understanding of a variety of learned categories. Our thesis is that the structural similarities between synaesthetic triggering stimuli and synaesthetic experiences are the remnants, the fossilized traces, of past learning challenges for which synasethesia was helpful.